Learning System of Research Ethics for EC Members in Bangladesh - Md. Monowarul Islam; Fahmida Faizha Shama (Bangladesh Journal of Bioethics, 2025)
The ethics committee (EC) promotes ethical evaluation of biomedical research to safeguard and well-being of all potential research participants. Assessment of research protocol, patient information leaflet, informed consent form, questionnaire, and any other supporting documents is a moral and legal obligation to EC. According to the WHO (World Health Organization), to be a member of EC requires a basic certification. However, this practice is uncertain in Bangladesh. This short communication highlights how EC members learn research ethics.